2007
DOI: 10.1002/pmic.200700281
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of differentially expressed proteins in Penaeus vannamei hemocytes upon Taura syndrome virus infection

Abstract: To understand molecular responses of crustacean hemocytes to virus infection, we applied 2-DE proteomics approach to investigate altered proteins in hemocytes of Penaeus vannamei during Taura syndrome virus (TSV) infection. At 24 h postinfection, quantitative intensity analysis and nano-LC-ESI-MS/MS revealed 11 forms of 8 proteins that were significantly up-regulated, whereas 9 forms of 5 proteins were significantly down-regulated in the infected shrimps. These altered proteins play important roles in host def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
58
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(69 citation statements)
references
References 42 publications
7
58
0
1
Order By: Relevance
“…Ferritin was also up-regulated in WSSV-resistant shrimp and in WSSV-challenged shrimp (2, 7). Carboxylesterase was also up-regulated at the protein level in taura syndrome virus-challenged shrimp (8). In the present study, induction of arginase and ribosomal protein mRNAs was also observed in this cluster during viral infection.…”
Section: Expression Profiling Of Genes Responsive To Yellow Head Virusupporting
confidence: 56%
“…Ferritin was also up-regulated in WSSV-resistant shrimp and in WSSV-challenged shrimp (2, 7). Carboxylesterase was also up-regulated at the protein level in taura syndrome virus-challenged shrimp (8). In the present study, induction of arginase and ribosomal protein mRNAs was also observed in this cluster during viral infection.…”
Section: Expression Profiling Of Genes Responsive To Yellow Head Virusupporting
confidence: 56%
“…In contrast, all six isoforms of cluster II had masses between 24 and 48 kDa, and higher pIs than isoforms from cluster I. An almost identical pattern of hemocyanin isoforms was observed in hemocytes of the Pacific white shrimp Penaeus vannamei upon virus infection (Chongsatja et al, 2007). Subsequent work showed that isoforms similar to those with low molecular mass in cluster II are peptides cleaved off the N-terminal hemocyanin sequence in white shrimp (Havanapan et al, 2009).…”
Section: Hemocyaninmentioning
confidence: 98%
“…Su contenido alergénico puede alterarse por diversos factores, como infección por virus, estrés por hipoxia y dieta en los cultivos de camarón (20)(21)(22)(23). En hemocitos del camarón L. vannamei se identificaron varios grupos de proteínas cuya expresión es regulada por la infección con el virus del síndrome de Taura (Taura Syndrome Virus, TSV) (24). Algunas de las proteínas alteradas participan en la respuesta inmunitaria del camarón, en transducción de señales, en el metabolismo de carbohidratos y en estrés celular; entre estas, se identificaron los alérgenos conocidos, Figura 1.…”
Section: Componentes Alergénicos En Los Extractos Preparados Para Diaunclassified